Digital Empowerment for Health Workers and Implications on EMRs Utilisation - Kanjo, Chipo; Hara, Joshua; Kaasbøll, Jens (Journal of Health Informatics in Africa, 2020)
Background and Purpose: Utilization of Electronic Medical Records (EMRs) bring many benefits to patient record handling. Previous research has shown that medical doctors in hospitals in Africa had poor IT skills, partly disabling their use of EMRs. Working in health centres, we wanted to know how to improve the digital skills of their personnel. Methods: Qualitative methods including interviews, informal discussions and observation were used for data collection. The study was conducted in three health facilities in Malawi, selected purposively as these were the ones implementing the EMR under study. The study targeted all staff that were capturing data at point of care using the app between January and June 2019. Results: Personnel in the health centres were computer illiterate, even if they used phones, and some smart phones. After computer training, they were still not comfortable using EMRs because their typing speed was delaying the process. Improving the typing speed allowed the users to comfortably use the EMRs. Three levels of EMR empowerment were identified; being able to 1) use EMR where typing speed is less relevant, 2) use EMR at point of care, 3) guide colleagues on their EMR use and find new ways of exploiting the technology. For reaching level 2, 50-100 hours of typing practice would be necessary. Conclusions: Health workers who lack computer skills tend to shy aware from using EMRs. Even if falling prices of equipment will enable more EMRs in rural areas, the digital empowerment process will still require significant resources.